Pengaruh Motivasi Kerja, Kerjasama Dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Mega Synergy Powerindo di Batam - Riana Riana; Mardiani Safitri; Hendri Herman (LPPM Universitas Jambi, 2022)
This research was conducted with the aim of knowing the influence of work motivation, cooperation and work experience on employee work productivity. The object of this research is PT Mega Synergy Powerindo (MSP) in Batam. The population in this study was 90 people. Determination of the number of samples using saturated samples where the entire population is used as a research sample. So that the sample in this study amounted to 90 respondents. The results of the study are that work motivation has an insignificant effect on employee work productivity, cooperation has a significant effect on employee work productivity, and work experience has an insignificant effect on employee work productivity. The R square value is 0.187 or 18.7%. This means that work motivation, cooperation, and work experience were able to explain work productivity by 18.7% while the remaining 81.3% was explained by other factors not included in the study.